The Nutritional Profile of Food Advertising for School-Aged Children via Television: A Longitudinal Approach - Daniel Campos; Mireia Escudero-Marín; Camila M. Snitman; Francisco J. Torres-Espínola; Hatim Azaryah; Andrés Catena; Cristina Campoy (Children, 2020)
The prevalence of childhood obesity continues to increase. Screen time, one of the most documented reasons for the obesogenic environment, enhances childhood obesity, since advertisements for unhealthy food products are still broadcast on channels for children. This is presently one of the main challenges for the government in Spain, since the current laws and obligations are not updated. This study aims to analyze food advertising aimed at children on Spanish television in 2013 and 2018 on children’s and general channels to test the effect of laws and obligations over time. In total, we viewed 512 h of the most viewed channels, two children’s and two general channels, during the week and on weekends during specific periods of 2013 and 2018. Food advertising was categorized as core, non-core, and other food advertisement (CFA, NCFA, and OFA, respectively) according to the nutritional profile. A total of 2935 adverts were analyzed, 1263 in 2013 and 1672 in 2018. A higher proportion of NCFAs were broadcast on children’s channels than in prior years, rising from 52.2% to 69.8% (p < 0.001). Nowadays, the risk of watching NCFAs on children’s channels compared to general channels turns out to be higher (Odds ratio > 2.5; p < 0.001), due to exposure to adverts for high-sugar and high-fat foods such as cakes, muffins, cookies, and fried and frozen meals rich in fat. In conclusion, the trends of nutritional profiles in food advertising on television are worsening over time, since the prevalence of NCFAs was higher in 2018 than in 2013. Currently, CFAs are not mainly broadcast on children’s channels, confirming high-risk exposure to non-core food advertising by watching them. Thus, food advertising laws and obligations should be adapted to increase compliance.